Associations Between Keratoconus and the Level of Sex Hormones: A Cross-Sectional Study - Zhao, Xiaorui; Yuan, Yifei; Sun, Tong; Zhang, Yu; Chen, Yueguo (Frontiers in Medicine, 2022)
Purpose: To analyze the level of sex hormone in relation to keratoconus (KC). Methods: Sixty-two eyes of 62 patients (12 females, 50 males) classified as KC and 120 eyes of 120 patients (21 females, 99 males) with mild to moderate myopia and astigmatism were analyzed. Plasma samples were collected and analyzed using a chemiluminescence immunoassay to determine the concentrations of estriol (E3), estradiol (E2), progesterone (P), and testosterone (T). Corneal morphological parameters, such as the central corneal thickness (CCT), thinnest corneal thickness (TCT), and maximum simulated keratometry (Kmax), were measured using Pentacam and Sirius. Results: The mean age was 23.73 ± 5.16 years for patients with KC and 23.68 ± 6.10 years for patients treated with laser vision correction (LVC). Among the patients with KC, 12 were female (19.35%) and 50 were male (80.65%). The majority of patients with KC were between 20 and 30 years old. In female patients, the concentration of T in the KC group was significantly lower than that in the LVC group (0.86 ± 0.33 nmol/L vs. 1.18 ± 0.58 nmol/L; P = 0.044). There were positive correlations between T, CCT (r=0.395, P=0.023) and TCT (r=0.378, P=0.030) in female patients. In male patients, E2 was higher in the KC group than the LVC group (143.75 ± 34.82 pmol/L vs. 124.80 ± 43.56 pmol/L; P = 0.013), while T was significantly lower (11.59 ± 2.85 nmol/L vs. 13.58 ± 4.77 nmol/L; P = 0.026). A positive correlation was found between E2 and Kmax (r=0.222, P=0.007) in male patients. Conclusions: Conclusively, our results showed that T level was reduced in both female and male KC plasma, while E2 was increased in male KC plasma. Different levels of sex hormones are correlated with KC, which, may provide the basis of a new technique for screening and diagnosing KC with or without the assistance of current imaging techniques. Moreover, the correlations between sex hormone alterations and KC provide compelling insight into KC etiopathogenesis.